2003
DOI: 10.2460/ajvr.2003.64.1369
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic evaluation of the gastroduodenal mucosa to determine the safety of short-term concurrent administration of meloxicam and dexamethasone in healthy dogs

Abstract: In healthy dogs, meloxicam appears to be safe with regard to adverse effects on the gastrointestinal tract. Concurrent administration of dexamethasone and meloxicam is more likely to cause gastric erosions than meloxicam administration alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
2
46
2
Order By: Relevance
“…Meloxicam is a selective COX-2 inhibitor, and the safety of meloxicam use in dogs has been previously described [10]. In the present study, there were fewer gastric mucosal adverse effects of combined meloxicam and prednisolone than in a previous study, in which the short-term concurrent administration of meloxicam (0.1 mg/kg, PO, q 24 hr) and dexamethasone (0.25 mg/kg, SC, q 12 hr) for 3 days caused more gastric erosions, but not gastric ulcers, than meloxicam alone [4]. Dexamethasone is thought to have more ulcerogenic power than prednisolone, and some reports have shown that a non-ulcerogenic dose of dexamethasone delayed gastric ulcer healing in animals [26,27].…”
Section: Disccusioncontrasting
confidence: 42%
“…Meloxicam is a selective COX-2 inhibitor, and the safety of meloxicam use in dogs has been previously described [10]. In the present study, there were fewer gastric mucosal adverse effects of combined meloxicam and prednisolone than in a previous study, in which the short-term concurrent administration of meloxicam (0.1 mg/kg, PO, q 24 hr) and dexamethasone (0.25 mg/kg, SC, q 12 hr) for 3 days caused more gastric erosions, but not gastric ulcers, than meloxicam alone [4]. Dexamethasone is thought to have more ulcerogenic power than prednisolone, and some reports have shown that a non-ulcerogenic dose of dexamethasone delayed gastric ulcer healing in animals [26,27].…”
Section: Disccusioncontrasting
confidence: 42%
“…Meloxicam is considered to be a COX-2 preferential (Smecuol et al, 2001;Plumb, 2002;Jones et al, 2002;Boston et al, 2003), and spare COX-1 activity as confirmed by in vitro and in vivo studies (Engelhardt et al, 1996a;Engelhardt et al, 1996b;Kay-Mugford et al, 2000;Jones et al, 2002). The relative selectivity of meloxicam for COX-2 may contribute to an improved tolerability profile compared with less selective NSAIDs (Vane, 1995;Fresno et al, 2005), resulting in reduced mucosal injury after its use (Smecuol et al, 2001).…”
Section: Introductionmentioning
confidence: 87%
“…It can be summarized that the therapeutic anti-inflammatory, analgesic, and antipyretic effects are due to the inhibition of COX-2. The undesirable gastrointestinal adverse effects, nephrotoxicity and coagulation disorders are believed to result from inhibition of COX-1 (Vane and Botting, 1998;Steinmeyer, 2000;Lichtenberger, 2001;Jones et al, 2002;Boston et al, 2003). Inhibition of COX-1 with a resultant decrease in endogenous prostaglandins critical to mucosal defence, especially PGE 1 (prostaglandin E 1 ), PGE 2 (prostaglandin E 2 ) and PGI 2 (prostaglandin I 2 ), is thought to be the most important mechanism of action of NSAIDs (Bowersox et al, 1996;Rich and Scheiman, 2000;Tomlinson and Blikslager, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Dexamethasone has been shown inhibitory effects of angiogenesis at the ulcer margins and baseline. Administration of corticosteroids along with NSAIDs leads to the formation of gastric mucosal lesions (Boston et al, 2003). Some studies had been shown that support the theory that corticosteroids alone lead to GI mucosal injury and hemorrhage (Rohrer et al, 1999).…”
Section: Etiopathogenesis Of Gastritis and Peptic Ulcer Diseasesmentioning
confidence: 96%